Depresion Diagnosis Application Using Beck Depression Inventory Method with Visual Novel Game - Moh Rizal Ihsanuddin; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2021)
Disturbance of feelings with sadness that continues in the long term is an explanation of depression, which can interfere with the social life of the person who experiences it (Pieter and Namora, 2012). As many as 86.94 (27%) in 322 billion individuals in the Southeast Asia region, making it the area with the highest Depression Rate. Because of this, it is necessary to have a Depression Diagnosis Application with the beck depression inventory method with a Visual Novel game approach to give a general idea of ​​whether the person has depression or not. The purpose of this study is to provide another alternative for users to find out whether they have depression or not with visual novel game media. This research method uses the Beck Depression Inventory where users are given 21 questions that must be answered to determine the level of depression they have. The test results on this game succeeded in detecting a person's level of depression which was proven by testing on 5 people with the results that 60% did not experience depression, 20% experienced mood changes and 20% experienced moderate depression. The result of this research is to produce a visual novel game with the application of depression diagnosis in it. This study is intended for people aged 15 years and over who feel they have symptoms of depression to find out their current condition.